Words of destiny : practicing astrology in North India - Guenzi, Caterina (Albany : State University of New York Press, 2021)
Investigates the professional practices of astrologers in urban India and their popularity among the educated middle and upper classes.
Second Year (Dvitīyavarṣa) -- Master's (Ācārya Parīkṣa) in Jyotiṣa -- Teaching Program (Pāṭhyakrama) -- First Year (Prathamavarṣa) -- Second Year (Dvitīyavarṣa) -- Glossary -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Translated from the French.
eBooks on EBSCOhost
Keywords: Hindu astrology -- Social aspects -- India -- Vārānasi (Uttar Pradesh); Predictive astrology; Astrologers -- India -- Vārānasi (Uttar Pradesh); Astrologie hindoue -- Aspect social -- Inde -- Vārānasi (Uttar Pradesh); Astrologie prédictive.; Astrologues -- Inde -- Vārānasi (Uttar Pradesh); SOCIAL SCIENCE / Anthropology / Cultural & Social; Astrologers; Hindu astrology -- Social aspects; Predictive astrology; India -- Vārānasi (Uttar Pradesh)